Impact of menopause on women with systemic lupus erythematosus. (December 2021) - Karvonen-Gutierrez, Carrie A.; Leis, Aleda
Highlights: Systemic lupus erythematosus (SLE) shows a strong female predominance, potentially due to sex hormones impact on disease. Those with SLE have increased and earlier risk for poor cardiovascular and bone health outcomes. Women with SLE may have an earlier menopause, which is also associated with cardiovascular and bone health risk. More research is needed about the treatment of menopausal symptoms for those with SLE given the existing risks. Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by chronic and systemic inflammation affecting multiple organ systems, including an increased risk of cardiovascular disease due to the SLE-associated hyperinflammatory state. SLE shows a strong female predominance, suggesting a potential role of sex hormones in the pathogenesis of the disease. Evidence suggests an earlier age of menopause among women with SLE, despite mixed findings regarding other markers of ovarian aging. In healthy populations, the menopausal transition is associated with important physiologic changes resulting in increased cardiometabolic risk and risk of osteoporosis. Thus, women with SLE who experience the inflammatory effects of the autoimmune condition combined with the (potentially earlier) menopausal transition may represent a particularly vulnerable group of individuals during a particular window of time. Little is known, however, about strategies for cardiovascular risk or bone loss mitigation in women with SLE during the menopausal transition. Further, despite lack of knowledge regarding the burden of menopausal symptoms in women with SLE, existing recommendations provide only cautionary guidance for the use of hormone replacement therapy to address menopausal symptoms in this population. Importantly, the data regarding both SLE and menopause-associated cardiovascular and osteoporotic risk demonstrate the critical need for additional research to identify the type and timing of treatments or interventions needed to best mitigate this increased risk.